Oral health literacy among mothers of pre-school children. - Tippanart Vichayanrat (2015)
Objectives: The aim of this study was to develop and validate a new oral health literacy test for Thai mothers. This study also examined the relationship among oral health literacy, oral health knowledge, socioeconomic factors and pre-school children’s oral health status. Materials and methods: The oral health literacy (OHL) test was developed to measure 3 aspects, which were basic/functional, communicative, and critical OHL. Mothers who brought their 2-6 years old children to the Pediatric Dental Clinic at Faculty of Dentistry, Mahidol University were invited to answer a self-administered questionnaire, which consisted of socio-demographic information and oral health knowledge (OHK), and OHL test. Caries status was collected from children’s dental records. Factor analysis was used to analyze a construct validity of the OHL test. Cronbach’s alpha was utilized to evaluate the internal consistency reliability of the test. Binary logistic regression was used to analyze the relationships among caries status, OHL scores, OHK, and socio-demographic variables. Results: The factor analysis extracted 4 components instead of 3 originally proposed in questionnaire, which suggested addressing the ‘searching and using information’ OHL aspect. The 25-item OHL test showed acceptable reliability (Cronbach’s alpha = 0.76). Mothers who correctly answered OHK items had significantly higher OHL scores, except the knowledge of cariogenic food. Less than 50 percents of mothers correctly understood the words ‘periodontal disease’, ‘root canal treatment’, ‘mottled tooth’, ‘scaling’, ‘bridges’, and ‘plaque’ (in Thai). Significant factors associated with children’s caries status were mother’s education (OR=9.1, 95% CI: 1.16-71.65), and OHL score (OR= 0.87, 95% CI: 0.76-0.98). Conclusion: The newly developed OHL test had acceptable validity and reliability to measure various aspects of oral health literacy. Mother’s education and oral health literacy were significant predictors to their children’ s caries status. This study reveals the complexity of OHL and help gaining the understanding of caregivers OHL in relation to knowledge and social variables.